Mine health and safety management - Karmis, Michael (Society for Mining, Metallurgy, and Exploration, 2001)
Mine Health and Safety Management presents aspects of management, leadership, regulation, and compliance that pertain to mining health and safety. It focuses on instilling a safety culture and fostering the ability to recognize and manage health and safety responsibilities and requirements. It details effective health and safety management systems and concentrates on safety and health hazard anticipation, identification, evaluation, and control. The book is intended for practicing engineers and supervisors, health and safety professionals, the research community, as well as undergraduate and g.